The Advantages of Android in Translation Course - andriani, Refika; kasriyati, destina (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2019)
This research aimed at describing the advantages of android use in learning process. This research conducted at the fourth semester of English Department of Education and Teachers Training Faculty of Universitas Lancang Kuning. The sample of this research is 30 % of the total number of the population, they are about 7 students. The method of this research is descriptive analysis. Before getting the data by giving questionnaire to the students during teaching and learning process of Translation Subject by using android, they had got a test of translating an English text into Bahasa Indonesia. Finally, it is found that there are some advantages found. They are android motivated the students, android is easy to use and access, android improve the students’ confidents to involve in the learning process.